0208 The Effect of Mastication on Psychomotor Vigilance Performance. (27th May 2020) - Hansen, D A; Hudson, A N; Lawrence-Sidebottom, D; Maislin, G; Miquel, S
Abstract: Introduction: Sustained attention is important for optimal neurobehavioral performance, but many biological and environment factors (e.g., circadian rhythm, distraction) may cause sustained attention deficits. Mastication (chewing) has been suggested to provide a countermeasure to sustained attention deficits. To investigate this, we conducted a randomized, within-subjects, cross-over study of sustained attention with a mastication condition and a control condition. Methods: N=58 adults (ages 18–45; 38 females) completed a 5h in-laboratory study. Subjects entered the laboratory at 09:00. Following training on performance tasks, they had a 1h break before beginning the first of two test bouts at 11:00. Each test bout was 40min long and included subjective rating scales, the Sustained Attention to Response Task, and the Psychomotor Vigilance Test (PVT). Here we focus on PVT lapses of attention (RT > 500 ms), false starts, and mean reaction time (RT) as measures of sustained attention. In between test bouts, subjects had a 1h break inside the laboratory. During one of the two test bouts, subjects were instructed to chew a piece of gum at a steady, comfortable rate. Mastication activity was verified via electromyography (EMG). Half of the sample was assigned to the mastication condition during the first test bout, the other half during the second test bout. Results: Controlling for order of conditions, there were no significant differences between conditions for PVT lapses (F1, 56 =0.40, P=0.54) or false starts (F1, 56 =0.10, P=0.80). Mean RT was higher in the mastication condition by 8.9±2.5ms (F1, 56 =12.68, P<0.001). Conclusion: Using this test paradigm, we were unable to detect any significant improvement in PVT performance, although mastication resulted in a very small increase in mean RT. However, subjects were not sleep-deprived, distracted, or otherwise perturbed. A follow-up study under conditions of sleep deprivation and/or with longer task duration may provide further insight into the countermeasure potential of mastication. Support: Mars Wrigley Confectionery, U.S., LLC